The Organization As A Gendered Entity: A Response to Professor Schultz’s the Sanitized Workplace - Lee, Rebecca K. (Columbia Journal of Gender and Law, 2006)
In the two decades since the Supreme Court first recognized the legal harm of sex harassment’ in Meritor Savings Bank v. Vinson, the trajectory of sex harassment law and policy continues to be controversial, even among gender scholars who seek to advance workplace equality but disagree about how to accomplish this objective. In this piece, I wish to contribute to the larger debate by offering a response to Professor Vicki Schultz’s provocative article, The Sanitized Workplace. Her project builds upon her previous works on sex harassment4 and the meaning of paid employment5 to put forth an innovative argument with significant implications in the areas of law, workplace culture, and organizational theory. While I support her endeavor in its larger intent, I write this response to examine her arguments and recommendations critically as well as constructively in an effort to engage in the ongoing task of advancing women’s aspirations in the work organization and the labor market. In The Sanitized Workplace, Schultz argues that the feminist movement to address sex harassment in the workplace echoes the ideological underpinnings of classical-management theory in that they both advocate for an emotion-free workplace, without harmful distraction, to maximize employee efficiency. She refers to a specific school of thought- the “scientific method” promoted by Frederick Winslow Taylor-to assert that the nascent organization was established as a rational space where laborers focused on production with little or no personal interaction. These early laborers were male, and Schultz points to the later entry of women into the workforce as introducing sexual elements into the workspace that would disrupt the rationality of organizational life, presenting a dilemma for managers who had sought to create an asexual work environment. As Schultz sees it, feminist reformers in our modem era ended up resuscitating the organizational practices of early bureaucratic leaders by similarly pushing for a desexualized workplace. In making this novel link between classical-management theory and the anti-sex harassment movement, Schultz is troubled by what she perceives to be unduly restrictive sex harassment policies currently in place in many work settings that reflect management’s early inclination to suppress laborers’ personal interactions of all kinds.10 According to her, sexual behavior should be allowed to openly flourish in the workplace, for she believes the freedom to express oneself in sexual terms enhances one’s social development at work and improves one’s productivity.’ She therefore wants to counteract the recent push for a return to the nonsexual workplace that supposedly predominated at the turn of the century.